2010
DOI: 10.1523/jneurosci.4394-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Nurture versus Nature: Long-Term Impact of Forced Right-Handedness on Structure of Pericentral Cortex and Basal Ganglia

Abstract: Does a conflict between inborn motor preferences and educational standards during childhood impact the structure of the adult human brain? To examine this issue, we acquired high-resolution T1-weighted magnetic resonance scans of the whole brain in adult "converted" left-handers who had been forced as children to become dextral writers. Analysis of sulcal surfaces revealed that consistent right-and left-handers showed an interhemispheric asymmetry in the surface area of the central sulcus with a greater surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 42 publications
3
42
1
Order By: Relevance
“…In that study, professional ballet dancers demonstrated a reduction in putaminal GM density compared with control subjects. Adult left-handed individuals who were forced to adopt right-handedness for handwriting at school also show a reduction in GM volume in the middle putamen 19. Based on these observations, one might speculate that chronically trained individuals with a high proficiency level in a specific motor skill may show a reduction in GM in the putamen because the high skill level makes the putamen less important to control their movements.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In that study, professional ballet dancers demonstrated a reduction in putaminal GM density compared with control subjects. Adult left-handed individuals who were forced to adopt right-handedness for handwriting at school also show a reduction in GM volume in the middle putamen 19. Based on these observations, one might speculate that chronically trained individuals with a high proficiency level in a specific motor skill may show a reduction in GM in the putamen because the high skill level makes the putamen less important to control their movements.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast to training related volume changes in the cortex, a recent VBM study with adult left-handed individuals who were forced to adopt right-handedness for handwriting at school showed a reduction in GM volume in the middle putamen 19. This region corresponds to the motor associative territory of the striatum.…”
Section: Introductionmentioning
confidence: 91%
“…In chimpanzees, a positron emission tomography study showed activation in the KNOB region in the hemisphere contralateral to the hand used during a reach-and-grasp task [Hopkins et al 2010b], suggesting that the KNOB may similarly represent the cortical substrate of the hand in this species. Finally, in both humans and chimpanzees, anatomical asymmetries in the KNOB have been linked to individual differences in hand preference and skill at the level of gross morphology [Amunts et al 1996; Foundas et al 1998; Hopkins and Cantalupo 2004; Kloppel et al 2010; Li et al 2009] and histology [Sherwood et al 2010; Sherwood et al 2007]. These findings reinforce the view that the motor hand area of the precentral gyrus may represent the neural substrate of the hand and possibly handedness.…”
mentioning
confidence: 76%
“…Finally, anatomical differences in the central sulcus (CS) have been linked to either experience-shaped or innate aspects of handedness. Indeed, whereas right-handers (RHs) display a leftward asymmetry in CS surface area, this asymmetry is inverted in left-handers (LHs), but not in LHs forced to use their right hand during childhood, illustrating the impact of motor experience on brain asymmetry (89). However, Sun et al (155) reported structural differences in the shape of the CS between RHs and both LHs or "left to right switched" handers.…”
Section: Functional Asymmetries Of the Human Brain And Neuroanatomicamentioning
confidence: 99%